PENGARUH MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF TERHADAP CARA BERKOMUNIKASI SOSIAL DALAM PEMBELAJARAN IPS KELAS 4 SD NEGERI 011 DUMAI - Hayatun Nufus; Muhamad Nukman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to find out whether interactive PowerPoint material has an impact on social communication in grade 4 social studies learning at SD Negeri 011 Dumai. With a one-group pretest-posttest design, this research is included in the pre-experimental design research category. The research participants were class 4 students at SD Negeri 011 Dumai with a total of 40 students, namely class 4A and 4B at SD Negeri 011 Dumai. Purposive sampling was used to determine the sample. Research findings show that PowerPoint learning media has a significant influence on the way of social communication. Thus, it can be said that the social communication strategies of grade 4 students at SD Negeri 011 Dumai are greatly influenced by the use of interactive PowerPoint materials in social studies classes.